KATA KERJA DALAM BAHASA INGGRIS DAN BAHASA TONSAWANG SUATU ANALISIS KONTRANSTIF - MOKOSOLANG, EKLESIA ELFI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â TheÂ researchÂ whichÂ entitledÂ â€œVerbsÂ inÂ EnglishÂ and TonsawangÂ Language:Â Â A Contrastive Analysisâ€ aims at identifying and analyzing the kinds of verbs in these two languages and finding out the differences between both languages. The English data have been collected from several books, internet, and some theory that related to this research, whereas the data of Tonsawang language have been collected by interviewing from some informants who know well about this language by using contrastive analysis approach. The data are then analyzed according to theory of Frank's (1972), there are two kinds of verbs, Classified by complement of verb: Predicating or linking verbs, transitive and intransitive verbs and reflexive verbs. Classified by form of verb: Auxiliary or lexical verbs, finite or non-finite verbs. To contrastive these two languages, the writer uses Lado (1957 ) concept. He said contrastive analysis is by contacting the language and the first language can be learned to propose and illustrate patterns that will lead to difficulties and ease of learning the language. The difference found in the English and Tonsawang verbs is found in the existing verb types. In English, found all types of verbs are classified by Frank (1972), whereas in Tonsawang language does not have any kind of linking verbs and non-finitive verbs. Â Theoretically, this research gives contribution toward the knowledge development in contrastive analysis especially verbs in English and Tonsawang language. Practically, this research can be used as a reference for further research. Key words: Kinds of Verb in English, Tonsawang Language and Contrastive Analysis